1995
DOI: 10.1016/0014-5793(95)01124-w
|View full text |Cite
|
Sign up to set email alerts
|

Point mutation of a conserved arginine (104) to lysine introduces hypersensitivity to inhibition by glyphosate in the 5‐enolpyruvylshikimate‐3‐phosphate synthase of Bacillus subtilis

Abstract: The role of a conserved arginine (R104) in the putative phosphoenol pyruvate binding region of 5-enolpyruvyl shikimate-3-phosphate synthase of Bacillus subtilis has been investigated. Employing site directed mutagenesis arginine was substituted by lysine or glutamine. Native and mutant proteins were expressed and purified to near homogeneity. Estimation of Michaelis and inhibitor constants of the native and mutant proteins exhibited altered substrate-inhibitor binding mode and constants. Mutation RI04K hyperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The DNA was digested with restriction endonucleases EcoRI, NcoI, and SalI and separated on 1% agarose gels. Southern blot analysis of digested DNA was done as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
“…The DNA was digested with restriction endonucleases EcoRI, NcoI, and SalI and separated on 1% agarose gels. Southern blot analysis of digested DNA was done as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
“…Since the substrates, phosphoenolypyurvate and shikimate-3-phosphate of EPSPs are anionic, it is reasonable to assume that they will be interacting with the basic amino acid residues. Appraisal of interaction of phosphoenolpyruvate with such residues has revelaed a catalytic and a non catalytic site (1,4). It has been demonstrated that substitutions R104K, R104Q, P105S, H385K (1) affect only the interactions of PEP and glyphosate with the enzyme without affecting the interaction of shikimate-3-phosphate with EPSPs.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier findings have established that substituting basic residues in the catalytic domain and C-terminal domain introduced significant changes in PEP binding and conformation of EPSPs (1). However, the Km for shikimate-3-phosphate remained unaffected (1,4). Thus, plethora of information is available on PEP interaction with the polypeptide, the interactive domain for the first substrate, shikimate-3-phosphate has not been well established.…”
Section: Vol 40 No 3 1996mentioning
confidence: 99%
See 1 more Smart Citation
“…The R100K mutation in E. coli EPSP synthase was made, but the K i (glyphosate) was found to be very similar to that of the wild-type enzyme (0.24 for R100K and 0.13 mM for wild-type) 27 . Unlike the R100K E. coli mutant, the R100K B. subtilis enzyme showed more sensitivity to glyphosate compared to the wild-type enzyme (K i = 0.06 for wildtype and 0.005 mM for mutant enzyme) 28 . Alignment of conserved regions of the translated amino acid sequences of EPSP synthases shows that P101 (E. coli) is not conserved in EPSP synthases.…”
Section: Discussionmentioning
confidence: 99%